Penilaian Atas Pengelolaan Keuangan Desa Menurut Permendagri Nomor 113 Tahun 2014 (Studi Kasus di Desa Lendang Nangka Kecamatan Masbagik) - Moh. Yusron Ali (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This research aim to to assess monetary management of countryside according to Permendagri number 113 year 2014 in case study in countryside of Lendang Nangka District of Masbagik. Subjek in this research is monetary management of countryside pursuant to Permendagri number 113 year 2014 and becoming this research object is countryside of Lendang Nangka district of Masbagik. Result of research is monetary management of countryside pursuant to Permendagri number 113 year 2014 about Management of Finance Countryside in done/conducted case study in countryside of Lendang Nangka district of Masbagik have pursuant to Permendagri number 113 year 2014. As for efficacy of Government of Countryside in executing applying of Permendagri number 113 year 2014 about Management of Finance Countryside is the existence of Human Resource adequate (SDM) and team cooperation or between Chief if the desk part of communicative in working regional goodness of Countryside office of Lendang Nangka and also moment reside in field to see problems that happened which is later; then made by reference device Regulation of Countryside about APBDESA. Keyword: monetary management, countryside finance, countryside